The effects of social media criticism against public health institutions on trust, emotions, and social media engagement - Jonathan Y. Lee (Proceedings of the National Academy of Sciences, 2025)
In recent years, trust in US public health and science institutions has faced unprecedented declines, particularly among Republicans/conservatives. To what extent might institutional criticism on social media be responsible for such politically polarized declines in institutional trust? Two online survey experiments (total N = 6,800), using samples roughly reflective of the US adult population, examined the effects of key types of criticism against the Agency for Healthcare Research and Quality (AHRQ) and the Centers for Disease Control and Prevention (CDC). The results suggest that just a single exposure to any of the key types of criticism was sufficient to undermine institutional trust. While an institutional rebuttal was partially able to reverse these effects, residual declines in trust were substantial enough to cause decreased intentions to adhere to the AHRQ/CDC health recommendation featured in the experiments. While institutions should, therefore, be concerned about all types of social media criticism, those featuring morally charged trust-undermining narratives attacking the integrity of the AHRQ/CDC generated dramatically more anger (i.e., moral outrage), which in turn attracted social media engagement preferences likely to promote viral spread and exacerbate preexisting institutional politicization and issue polarization. These results suggest that efforts to bolster institutional trust should pay special attention to criticisms featuring integrity-based trust-undermining narratives.